1999
DOI: 10.1093/emboj/18.11.2961
|View full text |Cite
|
Sign up to set email alerts
|

The Qo site of cytochrome b6f complexes controls the activation of the LHCII kinase

Abstract: We created a Qo pocket mutant by site-directed mutagenesis of the chloroplast petD gene in Chlamydomonas reinhardtii. We mutated the conserved PEWY sequence in the EF loop of subunit IV into PWYE. The pwye mutant did not grow in phototrophic conditions although it assembled wild-type levels of cytochrome b 6 f complexes. We demonstrated a complete block in electron transfer through the cytochrome b 6 f complex and a loss of plastoquinol binding at Qo. The accumulation of cytochrome b 6 f complexes lacking affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
184
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(194 citation statements)
references
References 66 publications
6
184
1
1
Order By: Relevance
“…Interaction between Stt7/STN7 and the Cytb 6 f Complex It is well established that the Stt7/STN7 kinase is closely associated with the Cytb 6 f complex (Lemeille et al, 2009) and that its activation is critically dependent on this association (Vener et al, 1997;Zito et al, 1999). Additional investigations using pull-down assays revealed that the interaction between this kinase and Cytb 6 f occurs through the Rieske protein (Lemeille et al, 2009).…”
Section: Effect Of High Light On the Redox State Of The Stt7/ Stn7 Kimentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction between Stt7/STN7 and the Cytb 6 f Complex It is well established that the Stt7/STN7 kinase is closely associated with the Cytb 6 f complex (Lemeille et al, 2009) and that its activation is critically dependent on this association (Vener et al, 1997;Zito et al, 1999). Additional investigations using pull-down assays revealed that the interaction between this kinase and Cytb 6 f occurs through the Rieske protein (Lemeille et al, 2009).…”
Section: Effect Of High Light On the Redox State Of The Stt7/ Stn7 Kimentioning
confidence: 99%
“…Excess excitation of PSII relative to PSI leads to reduction of the PQ pool and thus favors the docking of PQH 2 to the Qo site of the Cyt b 6 f complex. This process activates the Stt7/STN7 protein kinase (Vener et al, 1997;Zito et al, 1999), which is closely associated with this complex and leads to the phosphorylation of some LHCII proteins and to their detachment from PSII and binding to PSI (Depège et al, 2003;Lemeille et al, 2009). Although both Lhcb1 and Lhcb2 are phosphorylated, only the phosphorylated form of Lhcb2 is associated with PSI whereas phosphorylated Lhcb1 is excluded from this complex (Longoni et al, 2015).…”
mentioning
confidence: 99%
“…Excess stimulation of PSII relative to PSI leads to a more reduced redox state of the plastoquinone pool that favors docking of plastoquinol to the Qo site of the Cyt b 6 f complex. This activates the thylakoid protein kinase Stt7/STN7 that is required for the phosphorylation of the light-harvesting system of PSII (LHCII; Depège et al, 2003;Bellafiore et al, 2005), an event that leads to the displacement of LHCII from PSII to PSI (state 2; Vener et al, 1997;Zito et al, 1999). This process is reversible as excess stimulation of PSI oxidizes the plastoquinone pool and leads to the inactivation of the Stt7/STN7 kinase and to the dephosphorylation of LHCII by the PPH1/TAP38 phosphatase (Pribil et al, 2010;Shapiguzov et al, 2010) and its return to PSII (state 1).…”
mentioning
confidence: 99%
“…A unique light-and redox-controlled protein phosphorylation system has evolved in plant thylakoid membranes for regulation of the photosynthetic process (1,2). Intrinsic protein kinases in chloroplast thylakoid membranes (3)(4)(5) are activated by light or reducing conditions and controlled by the reduction of plastoquinone and its binding to the reduced cytochrome bf complex (6,7). Additional modulation of protein phosphorylation in thylakoid membranes involves the thiol redox state (8,9) as well as light-modulated conformational changes of substrate proteins (10).…”
mentioning
confidence: 99%